HIV, hypertension and diabetes care and all-cause mortality in rural South Africa in the HIV antiretroviral therapy era: a longitudinal cohort study - Mark Siedner; Emily Wong; Lusanda Mazibuko; Kashfia Rahman; Taing N Aung; Jacob Busang (BMJ Publishing Group, 2023)
Introduction South Africa is in the midst of rapid epidemiological transition from extremely high HIV and tuberculosis (TB) mortality to one characterised increasingly non-communicable disease-related deaths. However, longitudinal data linking modifiable risk factors and disease care indices to mortality in the country are extremely rare, and a prerequisite to appropriately prioritise health system responses.Methods Individuals in the Africa Health Research Institute Southern Demographic Health Surveillance area were invited to health fairs to collect data on modifiable risk factors and HIV, TB, diabetes and hypertension disease status and control. Individuals are then followed longitudinally through routine surveillance to detect deaths. We fit Cox proportional hazards models and estimated population-attributable fractions (PAFs) to identify modifiable risk factors and disease control indicators associated with all-cause mortality.Results A total of 18 041 individuals completed health screening and were followed for 114 692 person-years. Men had higher mortality rates than women across all age bands. The median follow-up time was 3.3 years (IQR: 3.0-3.5 years). For men, communicable diseases accounted for a higher PAF of mortality (PAF=13.7% for HIV and 8.3% for TB) than non-communicable diseases (6.6% for hypertension and 1.9% for diabetes). By contrast, despite extremely high HIV prevalence, non-communicable diseases with comorbid communicable disease accounted for the greatest share of deaths. In both sexes, having a chronic disease with poor control was most predictive of all-cause mortality. For example, among men, compared with those without each condition, adjusted HRs of all-cause mortality for people with uncontrolled disease were 3.47 (95% CI 2.10 to 5.72) for HIV, 1.52 (95% CI 1.05 to 2.20) for hypertension and 2.34 (95% CI 1.75 to 6.79) for diabetes. Among women, these same ratios were 5.32 (95% CI 3.54 to 7.99) for HIV, 1.73 (95% CI 1.31 to 2.28) for hypertension and 3.11 (95% CI 2.02 to 4.77) for diabetes.Discussion Poor control of chronic, treatable diseases predicts all-cause mortality in rural South Africa in the HIV antiretroviral therapy era. Health system strengthening to improve chronic disease and multimorbidity care should be prioritised.